AASA - Atividades de Aplicação em Sala de Aula: desafios e potencialidades da utilização de atividades investigativas no processo de ensino-aprendizagem de biologia para o ensino médio - Danielly Mara Silva (2023)
The Biology teaching learning process in high school is challenging for teachers, students, and other educational agents. The way teaching is mainly conducted in the country, using only reading textbooks, memorizing terms and concepts, and without room for experimentation and error, makes this discipline uninteresting and arid. There is a reasonable consensus that Biology teaching involving active methodologies, more specifically, using the inquiring approach, provides students with a critical, pleasurable, and thought provoking view of how science is produced. In 2017, to oppose this scenario, the Professional Master's Program in Biology Teaching PROFBIO was created. One of its central points is to enable teachers to experience Biology teaching as an experimental science with inquiring activities. As part of the activities developed in the Program, master's students prepare pedagogical proposals called Application Activities in the Classroom (AASA) every six months, using an inquiring approach. These AASA are developed with high school students, where master's students are Biology teachers. The present work intended to evaluate the challenges, potentialities, and effects of applying AASA in the Biology teaching learning process for high school students from public schools where PROFBIO master's students work. To support this analysis, a qualitative study of the effect of AASA in Biology classes at a public school in Minas Gerais, Brazil, and the evaluation of the perception of master's students and professors of the Program were carried out through the application of semi structured questionnaires. After applying the AASA and analyzing the interviews with master's students and professors, it was possible to detect the positive impact that the strategy generates both in higher education, as it favors the academic improvement of master's students, and in secondary education, preparing high school teachers to conduct classes that encourage student involvement. Among the main findings, we can highlight the perception that, for a better use of their potential, master’s students must have, from the beginning of the course, classes that approach and appropriate inquiry teaching. So, when applying the AASA in schools where they teach, they already have mastery and experience of this teaching methodology. The possibility of a PROFBIO repository to disseminate the AASA was also considered in this work, as it would allow other Biology teachers to use the didactic sequences in their classes. This action would promote the Biology teaching learning process as an experimental science and directly contribute to improving the quality of Primary and Secondary Education in the country.